2015
DOI: 10.1007/s10660-015-9193-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing e-government use in non-urban areas

Abstract: Evidence suggests that citizens outside larger urban centers are less prone to use the various functionalities of e-government, while they are the most likely to benefit from these services. Few studies have been performed to understand rural citizens' attitudes. Our purpose was to identify factors that influence the use of e-government services in outlying regions in the Province of Quebec (Canada). Our study was based on a subset of attitude-related variables that were shown to be strong predictors in prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
(28 reference statements)
0
29
1
Order By: Relevance
“…To discuss the influence of trust in context of egovernment services, it was observed that previous literature has identified trust as the most significant factor towards citizen's intention to use egovernment services (Abu-Shanab, 2014; Alsaghier and Hussain, 2012;Ranaweera, 2016;Rehman et al, 2016;Roy et al, 2015). Trust has been mentioned as an essential requirement for the successful implementation of e-government services.…”
Section: Results and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To discuss the influence of trust in context of egovernment services, it was observed that previous literature has identified trust as the most significant factor towards citizen's intention to use egovernment services (Abu-Shanab, 2014; Alsaghier and Hussain, 2012;Ranaweera, 2016;Rehman et al, 2016;Roy et al, 2015). Trust has been mentioned as an essential requirement for the successful implementation of e-government services.…”
Section: Results and Data Analysismentioning
confidence: 99%
“…Similarly, Mohajerani et al (2015) stated that privacy and security concerns have a positive impact on trust in e-government services. There are some studies where the factors associated with risk are addressed directly towards an attitude in using a technology (Roy et al, 2015). However, the importance of risk is always highlighted as a significant factor in using government services.…”
Section: Results and Data Analysismentioning
confidence: 99%
“…From another perspective, the early stage of eG implementation mostly concentrated in developed countries like Canada (Roy et al, 2015), parts of Europe (Graafland-Essers and Ettedgui, 2003), Turkey (Ozkan and Kanat, 2011), Netherlands (Horst et al, 2007), Singapore (Chan et al, 2008;Teo et al, 2009), the UK (Beynon-Davies and Williams, 2003;Hamilton et al, 2011), Taiwan (Hung et al, 2006;Chu et al, 2004) and the USA (Lee et al, 2003;Yun and Opheim, 2010). Similarly, developing countries, such as Malaysia, Indonesia, India and Bangladesh, also realised the importance of eG (Lean et al, 2009;Kumar and Best, 2006;Rokhman, 2011).…”
Section: Eg Projects and Issuesmentioning
confidence: 99%
“…For e-government to function, certain necessary factors and components are vital. To mention a few, they are perceived usefulness of the system, perceived ease of use, perceived service quality, perceived risk, trust in government and the system, technological infrastructure such as telecommunications, literacy, and many more [5][6][7].…”
Section: Introductionmentioning
confidence: 99%